The Antioxidant Activities and Phenolic Content of Improved Soybean Seeds Varieties of Different Grain Sizes - Muchdar Soedarjo; Suhartina Suhartina; Novita Nugrahaeni; Andy Wijanarko; Devi Anggraini Putri; Sri Fatmawati (IPTEK The Journal for Technology and Science, 2020)
Tempe and tofu are the main product of soybean commonly consumed as a daily food for the people of Indonesia. So far, soybean is well known to be a source of protein. Indeed, soybean contains secondary metabolites resulting in antioxidant activities. Antioxidants would nullify the negative effect of reactive oxygen and, as a result, could improve and maintain human health. Improvement of awareness of Indonesian people that soybean is good for human health promotion and maintenance could be a trigger to enlarge the soybean production area and increase national soybean production. The present study was undertaken to evaluate the total phenolic content and antioxidant activity of some improved soybean varieties. The observation was done in three replicates, and the standard deviation was made. The results of the present study showed that total phenolic content and antioxidant activity, as measured by ABTS and DPPH, varied among the soybean seeds tested. The variability of total phenolic content and antioxidant activity was not caused by different seed sizes but by the different genetic background encoding for other phenotypes than the seed size. In general, antioxidant activity is positively correlated to total phenolic content. Demas and Tanggamus showed significantly higher antioxidant activity compared to the rest, including imported soybean. Therefore, Demas and Tanggamus could be used as better food sources for human health.